Interprofessional collaboration and job satisfaction in German intensive care units: a cross-sectional survey within the PRiVENT project - Fleischhauer, Thomas; Biehler, Elena; Michels-Zetsche, Julia D.; Trudzinski, Franziska; Schubert-Haack, Janina; Forstner, Johanna; Schneider, Armin; Kempa, Axel; Joves, Biljana; Neurohr, Claus; Herth, Felix; Szecsenyi, Joachim; et al. (Respiration, 2025)
Introduction: The multicentre cluster-randomized PRiVENT study aims to improve weaning of long-term ventilated patients in German intensive care units via a complex interprofessional intervention. To assess perceptions on interprofessional collaboration and job satisfaction among different health professions, a survey was conducted in four clusters, each comprising one weaning centre and 7-12 cooperation hospitals. Methods: Three validated questionnaires were used to measure (a) interprofessional socialization (7-level Likert scale), (b) interprofessional collaboration (5-level), and (c) job satisfaction (7-level). Alongside a descriptive analysis, a subgroup analysis was performed comparing mean scores between physicians and non-physicians and the four clusters. Correlation coefficients were calculated to check for correlations of age group and work experience with interprofessional collaboration and job satisfaction. Results: Sixty-two questionnaires were returned by health workers of the intensive care units, corresponding to a response rate of 47%. Respondents rated interprofessional socialization (5.7 ± 0.6) and collaboration (3.8 ± 0.6) as good. Job satisfaction was high (5.1 ± 1.0), particularly regarding the collegial environment and variety of work tasks. Satisfaction with physical workload, income, and working hours was lower. Compared to physicians, overall ratings of non-physicians were lower, although the differences were not statistically significant, as were those between clusters. There was a statistically significant positive correlation of age group and work experience with overall job satisfaction. Conclusion: Health workers within PRiVENT are satisfied with their workplace conditions and rate interprofessional collaboration as good. Follow-up surveys will provide insights into the impact of PRiVENT on interprofessional cooperation and job satisfaction.